2023
DOI: 10.1021/acsmaterialslett.3c01218
|View full text |Cite
|
Sign up to set email alerts
|

RuIn Solid-Solution Alloy Nanoparticles with Enhanced Hydrogen Evolution Reaction Activity

Xin Zhou,
Megumi Mukoyoshi,
Kohei Kusada
et al.

Abstract: We report the synthesis of novel RuIn solidsolution alloy nanoparticles (NPs) via the electrochemical cleaning of RuIn@InO x NPs. By alloying In to Ru, the RuIn NPs exhibited enhanced hydrogen evolution reaction (HER) activity compared with monometallic face-centered cubic (fcc) Ru NPs. Furthermore, the HER activity of RuIn NPs was comparable to that of commercial Pt catalysts. At a current density of 10 mA cm −2 , RuIn NPs displayed a lower overpotential of 30.7 mV compared to monometallic fcc Ru NPs (57.8 mV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Recently, solid-solution RuIn alloy NPs with an fcc crystal structure have been obtained, and they are reported to exhibit enhanced HER performance. 25 To date, no research has been reported on the effect of the crystal structure of RuIn solid-solution alloy NPs on catalytic properties due to the difficulties associated with controlling the crystal structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, solid-solution RuIn alloy NPs with an fcc crystal structure have been obtained, and they are reported to exhibit enhanced HER performance. 25 To date, no research has been reported on the effect of the crystal structure of RuIn solid-solution alloy NPs on catalytic properties due to the difficulties associated with controlling the crystal structure.…”
mentioning
confidence: 99%
“…According to our previous work, fcc RuIn NPs were obtained by wet chemistry and a cyclic voltammetry (CV) cleaning method. 25 The carbon-loaded fcc RuIn NPs were heated under a H 2 atmosphere to cause a phase transition from fcc to hcp. Experimental details are given in the ESI †…”
mentioning
confidence: 99%